THE DEPRESSION IN THE PROCESS OF SENESCENCE AND THE FRAGILITY OF THE COGNITIVE FAMILY SUPPORT - Regina Pacheco Soares, Márcia; Pacheco Soares, Thaís; Gonçalves Fernandes, Fernanda; Santos Crespo Istoe, Rosalee (LINKSCIENCEPLACE, 2026)
Elderly depression is one of the causes related to the impairment of their cognitive functions and has as characteristic the loss of motivation to carry out activities, social participation with damages to the autonomy and maintenance of an active life. The family is the main source of support and care for the elderly depressed. Brazilian demographic and social transformations have caused changes in family structures causing sociodemographic, cultural and financial impacts that affect the way of caring for the elderly. In this context, the present study aim investigates how these changes interfere in the family's reception of the depressed elderly. It is a bibliographic study of exploratory and descriptive character and with qualitative approach. The results showed that, in the majority of cases, depressed elderly people receive care from female relatives; often caregivers are also elderly, with physical and / or emotional health fragility. Changes in family structures and composition, poverty, reduction in the number of children and the women employment have been found to affect the family capacity of host depressive elderly.